A Cost-Benefit Analysis of Marine Conservation Efforts - Rajan, S.S.; Fernandes, Ruban Baltazar (International Journal of Accounting and Economics Studies, 2025)
Overexploitation is a widespread issue in fisheries worldwide. The fishing industry in India is not an exception. The Indian Ocean's marine fisheries resources have drastically decreased. Biological overfishing occurs when the pace of harvesting exceeds the natural rate of renewal. Most Indian fishermen made their living under hazardous and vulnerable circumstances, according to literature on the country's fisheries. Numerous challenges are linked to deep-sea fishing, including the extensive use of vessels along the upper East coast, the overexploitation of specific species, capital-intensive operations, and the general limitation of fishing activities to areas within a depth of 40 fathoms. Additionally, the annual discarding of approximately 130,000 tonnes of unwanted fish and the considerable fishing pressure on shrimp resources further exacerbate these issues. Similarly, artisanal capture fisheries face their own set of problems, such as overfishing, the use of detrimental fishing techniques, damage to natural ecosystems, conflicts with other industries, fishing in unconventional areas, and the mismanagement and wastage of surplus catches. In essence, unsustainability and overcapacity are two aspects of the same issue. The absence of clearly defined property rights in fisheries is the primary cause of surplus capacity. Most commercially exploited stocks exhibit signs of overexploitation, putting the nation's fisheries resources under stress in various regions. The livelihoods of those who depend on these resources are affected by this.